Application of Arcgis Software in the Production of Standard Subdivision Map in Land Engineering - Zhang, Lu; Shi, Lei (Scientific Journal of Technology, 2025)
The rapid development of the economy and society has led to a rapid expansion of the volume of territorial and resource data in China, which has brought certain difficulties to the development of the land engineering industry. However, ArcGIS software not only overcomes many inconveniences in land data statistics, but also can be applied to all aspects of land use change. It can modify, organize and output the final change statistics summary table of the huge volume of territorial data in land engineering one by one. The operation is simple and the query is convenient. This article analyzes the application of ArcGIS software in the analysis of unused land reserve resources, the production of standard sheet maps, and the superimposition of surveying and mapping and land use status maps in land engineering one by one, and points out that the development prospects of ArcGIS software in the field of land engineering are huge, ultimately achieving the goal of efficient utilization and development of land resources in China.